순창군 서부권(복흥, 쌍치, 구림) 장기 발전 계획 - 김정섭 (한국농촌경제연구원, 2009)
The world is witnessing today accelerated opening of agricultural markets driven by the WTO, conclusion of FTAs between countries, and changes in the agricultural policies to focus on multi-functionality of agriculture. Theses changes are making a huge impact on domestic agriculture and local administrations as well as rural development plans. In this respect, making agricultural and rural plans is becoming more significant. This research tried to establish comprehensive preliminary plans for the west area of Sunchang-gun. The socio-economic characteristics of this area(Bokheung, Ssangchi, Gurim) are examined in depth. Also, potential of the major agricultural products and amenities are evaluated. People living in these areas assessed their own development needs. An assessment of strong and weak points is also made to come up with a comprehensive development plan for the agriculture and rural communities. Based on the research results of this study, we proposed 'Organic Agriculture, Attractive Rural Tourism, Learning Organization' as the vision for the west area of Sunchang-gun. In this regard, the following three strategies are suggested to realize the vision. First, R&D of the specialized products exploiting the specialized crops(Red Berry, Blue Berry, Soybean etc) in this area should be reinforced. Also, processing firms, logistic facilities, and training programs should be developed. Second, the touristic potential should be realized by means of bottom-up approach. Many communities should cultivate their amenities by their own. Local government and NGOs should be able to support those efforts. Third, the local government should make farmers' capacity building programs. Capacity building programs can be implemented in the forms of 'farmers' learning organization'. Researchers: Jeong-Seop Kim, Kwang-Sun Kim, In-Hye Kwon, Mi-Ryung Song Research period: 2008. 7. - 2009. 1. E-mail address: jskkjs@krei.re.kr